The risk appetite of development finance institutions (DFIs) and funding for start-ups in South Africa - Nkosi, Thabiso (Research of GSB, 2018)
Using publicly available data from three South African Development Finance Institutions (DFI's), this study examines the risk appetite of Business Partners (BP), the National Empowerment Fund (NEF) and the Small Enterprise Finance Agency (SEFA). This study analyses data between 2011 and 2015 to determine the DFI's risk appetite and to identify key determinants of risk appetite with regard to funding SMEs, specifically startups. The study's findings reveal that South African DFI's have a high to extremely high-risk appetite level and that state-owned DFI's, NEF and SEFA have a higher risk appetite for funding SMEs specifically startup related loan products than private DFI BP. The study's findings also illustrates that South African DFI's risk appetites have a weaker negative relationship with shorter-term financial products than longer-term financial products indicating a higher risk appetite for funding shorter-term financial products.